Juxtaposing a cultural reading of landscape with institutional boundaries: the case of the Masebe Nature Reserve, South Africa. (16th November 2016) - Boonzaaier, Chris; Wels, Harry
Abstract: The article explores theoretically the juxtaposition of local stories about landscape with institutional arrangements and exclusionary practices around a conservation area in South Africa. The Masebe Nature Reserve is used as a case study. The article argues that the institutional arrangements in which the nature reserve is currently positioned are too static, and consequently exclusionary, in their demarcation of boundaries. This stifles local communities' sense of belonging to these landscapes. Hence, they strongly resent and feel alienated by the nature reserve. Their opposition and alienation often manifests in poaching. The empirical material is based on how local people living adjacent to the Masebe Nature Reserve have historically named and interpreted the area's impressive sandstone mountains, in the process creating a sense of belonging. Juxtaposing this mostly tranquil cultural reading of the landscape to the institutional practices of boundary demarcation gives the analysis an immediate critical edge regarding issues of social justice